Design and stability analysis of a control system for a grid-independent direct current microgrid with hybrid energy storage system. (July 2021) - Singh, Prashant; Lather, J.S.
Highlights: Proposed control method's design and stability analysis for hybrid energy storage systems to maintain demand-generation inequality and DC bus voltage regulations is presented. The proposed control method effectively maintains the DC bus voltage within the permissible ±5% allowed range. Effective power-sharing within HESSs for considered events are presented. Total harmonics distortion analysis of three-phase AC load is also performed. Simulation results have been experimentally verified with hardware-in-loop on field programmable gate array based real-time simulator. Abstract: This paper proposes the design and stability analysis of a control system for a hybrid energy storage system (HESS). The control method is framed to address the demand-generation disparity and DC bus voltage regulation. In the proposed control method, battery is utilized to address slow-frequency power surges. Meanwhile, supercapacitor (SC) has been used to manage fast-frequency power surges. Furthermore, the proposed control method enhances the battery life cycle by diverting uncompensated battery currents to SCs for quick compensations. The advantages of the proposed control method over the conventional control method show its robustness for DC bus voltage in terms of settling time and voltage overshoot/undershoot. Additionally, total harmonic distortion (THD) of 3-phase voltage is presented. The test scenarios have been verified in a MATLAB/SIMULINK environment. The experimental results authenticate the viability and feasibility of the proposed control method. Graphical abstract: Image, graphical abstract